The Effect of Organic Fertilizer Dosage and Planting Distance on the Growth and Yield of Kale (Brassica oleracea L. var. Acephala) - Raissa, Widya Shafa; Widiwurjani, Widiwurjani; Suryandika, Fadila (Jurnal Biologi Tropis, 2025)
Organic fertilizers, such as earthworm fertilizer, and adjusting planting distances to meet plant demands can boost kale plant yields, particularly curly kale. The purpose of this study was to determine the effect of organic fertilizer dosage and planting distance on the growth and yield of kale (Brassica oleracea L. var. Acephala). The research method used a Split Plot Design approach involving two main treatment factors. The results found that the combination of 9 tons/ha (2.16 kg) of manure and a planting distance of 40 x 40 cm produced the best results for crown diameter. The combination of 6 tons/ha (1.44 kg) of manure and a planting distance of 20 x 40 cm gave the best results for fresh root weight per plant at harvest. All criteria were not significantly affected by the use of manure. The treatment of a planting distance of 30 x 40 cm gave the best results for plant height, which was 31.96 cm. Regarding the findings of this study, further researchers can conduct soil analysis before administering the manure coat and re-analyze it after 1 month of administration to determine the quality of the fertilizer content and pay attention to the balance of planting distance for plants, so as to prevent the emergence of diseases caused by high humidity and nutrient competition between plants. Fertilization can also be given to increase yields. The conclusion is that the administration of organic fertilizer doses and planting distances affect the growth and yield of Water Spinach (Brassica oleracea L. var. Acephala).